A Critical Look at Digital Media, the Intellectual Property Regime and Free Open Source Software - Yılmaz Alışkan (Erciyes İletişim Dergisi)
This article examines how the intellectual property regime works in digital media and how free open source software is pushing the boundaries of the regime on the digital realm. The main purpose of this article is to highlight the differences that models of knowledge production can make in the process of building a participatory society. This article uses Michael Gibbons' Mode 1 and Mode 2 theories as a method. In the light of this theory, power relations in the production and distribution of knowledge are discussed. The Mode 2 model points to a commons-based model of knowledge production that has a democratic potential. The intellectual property regime is struggling to control the flow of information on the internet. It is quite difficult for the intellectual property rights regime to control the circulation of knowledge on the Internet, as digital media play a key role in the free flow of knowledge. Free open source software is an effective model for those who support the free flow of information in the digital space.